Rancang Bangun Rekapitulasi E-Presensi Dosen PNS-DPK Dilingkungan LLDikti Wilayah II - Muhamad Ariandi; Oktaviana Destri Lestari (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
Higher Education Service Institutions (LLDikti) are government work units in certain areas whose function is to help improve the quality of higher education administration established by the Minister. Higher Education is an educational institution in the form of academics, high schools and universities. Universities consist of educators (lecturers) and students. One of the lecturers' duties is to record the presence and activity of each tertiary institution which affects the salary system that will be received, but the attendance system that is carried out still uses the way to fill in the presence found on the Google form. So that it is necessary to do a design that aims to monitor and design an information system for recapitulating the attendance list of PNS-DPK LLDikti lecturers in Region II and as a basis for paying salaries in accordance with the recap results that have been approved by superiors. The method used in this study is the SDLC method, because the SDLC method is able to adjust the results that the researcher wants to produce. So that the results of attendance reports submitted are appropriate and faster with the integration from PT to LLDikti Region II.